The influence of root-crack dynamics on soil water infiltration across seasonal variations - Yuliana Yuliana; Arwan Apriyono; Reza Pahlevi Munirwan; Song Feng; Viroon Kamchoom‬ (Smart Agricultural Technology, 2025)
• Double ring test was used to measure infiltration rate along wetting-drying changes • Vetiver root dynamics and soil cracks controlled infiltration over 18 months. • Bare zones had higher CIF compared to vegetated zones across all seasons. • All zones showed an increased CIF and infiltration during dry periods, with decreased in wet periods. • Vegetated zones exhibited 8times higher infiltration rates than bare zone. Soil infiltration plays a vital role in the hydrological cycle, impacting water absorption and availability for crops. Accurate infiltration measurements are crucial for improving water management in agricultural systems. This study observed the interaction of root growth and crack to the infiltration rate with influence of wetting drying conditions. Over an 18-month period, a double-ring infiltrometer test was applied to directly assess infiltration rates in both bare and vegetated zones. A minirhizotron camera was used to capture the root growth and decay defined as Root Area Ratio (RAR) and crack defines as crack intensity factor (CIF). The findings reveal that root growth peaked at 6.3% during the first cycle but declined to 4.5% in the second dry summer due to water stress and root decay. Vegetated zone also experienced lower CIF compared to bare zone. Infiltration rates increased significantly during dry periods, with the bare zone reaching a final rate of 1.63 × 10⁻⁶ m/s and vegetated zones showing up to an 8-fold increase in the second cycle. These findings underscore the critical role of root dynamics and soil cracking in regulating water infiltration. For agricultural systems, understanding these processes is essential for developing effective soil management and irrigation strategies that improve infiltration, enhance soil stability, and optimize crop productivity.
Keywords: Plant nutrient uptake and metabolism; Soil and Unsaturated Flow; Soil Moisture and Remote Sensing